2012
DOI: 10.1128/jcm.06462-11
|View full text |Cite
|
Sign up to set email alerts
|

Association between β-Lactamase-Encoding bla OXA-51 Variants and DiversiLab Rep-PCR-Based Typing of Acinetobacter baumannii Isolates

Abstract: bThis study investigated the correlation between bla OXA-51 variants and Acinetobacter baumannii worldwide clonal lineages 1 to 8 (WW1 to -8). The bla OXA-51-like genes of 102 A. baumannii isolates were sequenced. Using DiversiLab repetitive-sequence-based PCR (rep-PCR) typing, 92 of these isolates had previously been assigned to WW1 to -8 and 10 were unclustered. Clustering of DNA sequences was performed using the neighbor-joining method and the Jukes-Cantor phylogenetic correction. bla OXA-51 variants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 23 publications
6
71
1
Order By: Relevance
“…Until now, this possibility was tested in parallel only with the PubMLST scheme (12), against which the bla OXA-51-like SBT was shown to identify accurately isolates belonging to the three major epidemic lineages. In another study, the bla OXA-51-like SBT compared with rep-PCR identified international clonal lineages I to III and worldwide clonal lineages 4 to 8 (17). In the current report, the performance of bla OXA-51-like SBT was compared with that of the Pasteur's MLST scheme, which does not exhibit recombination in its target loci in contrast with PubMLST, and also with that of 3-LST, including both the initial multiplex PCR and the sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, this possibility was tested in parallel only with the PubMLST scheme (12), against which the bla OXA-51-like SBT was shown to identify accurately isolates belonging to the three major epidemic lineages. In another study, the bla OXA-51-like SBT compared with rep-PCR identified international clonal lineages I to III and worldwide clonal lineages 4 to 8 (17). In the current report, the performance of bla OXA-51-like SBT was compared with that of the Pasteur's MLST scheme, which does not exhibit recombination in its target loci in contrast with PubMLST, and also with that of 3-LST, including both the initial multiplex PCR and the sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The dendrograms show the amounts of genetic change based on multiple alignments and were generated using phylogeny.fr software (17). The bar at the bottom of each figure shows the amount of genetic change corresponding to the length of each branch.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, sequencebased typing (SBT) of bla OXA-51-like gene variants was reported to have potential for use in the epidemiological characterization of A. baumannii isolates obtained from various locations in Europe. bla OXA-69 , bla OXA-66 , and bla OXA-71 are the predominant members of closely related bla OXA-51-like subgroups, which are associated with European clone I (EUI), EUII, and EUIII, respectively [14][15][16]. However, few studies have investigated the correlation between bla OXA-51-like variants with MLST typing.…”
Section: Discussionmentioning
confidence: 99%
“…Although MLST has many advantages, it is a robust scheme that is often time-consuming, expensive, and labour-intensive [14]. Currently, several studies have reported that sequence-based typing (SBT) of bla OXA-51-like gene variants has potential for application to assess the epidemiological characterization of A. baumannii [14][15][16], but more data are needed.…”
Section: Introductionmentioning
confidence: 99%